Relation of the Severity of Obstructive Sleep Apnea in Response to Anti-Arrhythmic Drugs in Patients with Atrial Fibrillation or Atrial Flutter - Monahan, Ken (2012)
Atrial fibrillation (AF) is more common in those with obstructive sleep apnea (OSA) than in unaffected individuals and recurs more frequently in the presence of severe OSA after electrical cardioversion and AF ablation. However, it is unknown whether severity of OSA influences the efficacy of anti-arrhythmic drug (AAD) therapy in patients with OSA and AF. This study examined the impact of OSA severity on treatment of symptomatic AF with AADs. We studied 61 patients (62 ± 15 years; 21 women) treated with AADs for symptomatic AF who had overnight polysomnography. Rhythm control was prospectively defined as successful if a patient remained on the same AAD therapy for a minimum of 6 months with ≥75% reduction in symptomatic AF burden. Twenty-four patients (40%) had severe OSA. Thirty patients (49%) were rhythm controlled with AADs. Non-responders to AADs were more likely to have severe OSA than milder disease (52% vs 23%; p < 0.05); those with severe OSA were less likely to respond to AADs than participants with non-severe OSA (39% vs 70%; p = 0.02). Non-responders had higher apnea-hypopnea indices than responders (34 ± 25 vs 22 ± 18 events/hour; p = 0.05), but there were no differences between these groups in minimum oxygen saturation or % time spent in REM sleep. In conclusion, patients with severe OSA are less likely to respond to AAD therapy for AF than those with milder forms of OSA.